Correlation of Maximum Phonation Time and Vocal Intensity With Intraluminal Esophageal and Pharyngoesophageal Pressure in Total Laryngectomees. (November 2014) - Takeshita-Monaretti, Telma Kioko; Dantas, Roberto Oliveira; Ricz, Hilton; Aguiar-Ricz, Lílian Neto
Objective: This study aimed to correlate maximum phonation time, vocal intensity, and dynamic extension with intraluminal esophageal and pharyngoesophageal segment pressure during tracheoesophageal phonation. Design: Prospective analysis. Setting: Tertiary academic hospital. Methods: The study was conducted on 20 total laryngectomees with alaryngeal speech and with secondary insertion of a tracheoesophageal prosthesis who were submitted to vocal recording of maximum phonation time and vocal intensity (minimum, habitual, and maximum). The participants were then submitted to manometry for the determination of the amplitude of intraluminal esophageal (proximal, middle, and distal) and pharyngoesophageal segment pressure during phonation. Results: A significant positive correlation was detected between habitual vocal intensity and the middle (0.004) and distal (0.05) esophagus, in addition to a correlation of maximum intensity with the middle esophageal portion (0.03). Dynamic extension showed correlation with the amplitude of esophageal pressure. There was no significant correlation between the variables studied and pressure of the pharyngoesophageal segment or between maximum phonation time and esophageal pressure amplitude. Conclusion: The middle and distal regions of the esophagus were found to be compliant, permitting an adjustment of vocal intensity. There was no correlation between maximum phonation time and the amplitude of esophageal and pharyngoesophageal segment pressure.